Impostor Phenomenon on First- and Second-year College Students - Fahira, Ulimaz Dea; Hayat, Bahrul (TAZKIYA Journal of Psychology, 2021)
New students tend to experience the stress and anxiety of transitioning from the school environment to the campus environment. Anxiety in dealing with new situations or roles can lead to the Impostor Phenomenon (IP). This study aimed to determine the effect of family relationships, general anxiety, and the Big-five personality traits on impostor phenomena. The sample of this study was 439 first and second-year students taken by the non-probability sampling technique. The measuring instruments used in this research are Clance Impostor Phenomenon Scale (CIPS), Brief Family Relationships Scale (BFRS), Four-Dimensional Anxiety Scale (FDAS), and Big-five Inventory (BFI). Data analysis in this study used Confirmatory Factor Analysis (CFA) and multiple regression analysis techniques. The results showed a significant effect of family relationships, general anxiety, and the Big-five personality traits on the impostor phenomenon. Based on testing the minor hypothesis, there are six significant variables: emotional, physiological, cognitive, behaviour, extraversion, and awareness. Other variables such as cohesion, expressiveness, conflict, agreeableness, neuroticism, and openness have no significant effect on the impostor phenomenon.